Applied ethnomusicology’s point of view: Redefining education based on local wisdom - Permatasari, Rr. Yudiswara Ayu; Irawati, Eli; Elasalama , Nadia (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
This research examines the redefinition of education based on local wisdom through applied ethnomusicology perspectives using philosophical research methods and literature study approaches. Applied ethnomusicology offers a comprehensive theoretical framework for understanding how traditional music and arts can serve as foundations for more contextual and meaningful educational systems. This study analyses literature on local wisdom concepts, applied ethnomusicology, and alternative educational systems to construct a new understanding of local culture-based education. Through philosophical analysis, this research reveals that local wisdom-based education is not limited to learning and applying traditional objects or artistic artefacts from a particular region. The research findings demonstrate that local wisdom-based education provides a broader perspective on intellectual wealth values within cultures grounded in regional characteristics and problem-solving systems possessed by local communities. These findings theoretically contribute to developing more inclusive, contextual, and meaningful educational models for students' character development and cultural identity formation. This perspective transforms education from artefact-centred learning to value-based cultural understanding encompassing indigenous knowledge systems and community-based solutions.